Association between endothelial nitric oxide synthase gene polymorphism (T-786C) and ischemic stroke susceptibility: a meta-analysis. (2nd September 2014) - Liu, Ruozhuo; Geng, Peiliang; Ma, Minghui; Yu, Shengyuan; Wang, Xiaolin; Zhang, Wei; Di, Hai
<x xml:space="preserve">Abstract</x> Background: The endothelial nitric oxide synthase (eNOS) T-786C polymorphism has been implicated in a number of studies investigating ischemic stroke (IS), yet previously published studies showed inconsistent results that recent meta-analyses have not resolved. Methods: In the comprehensive meta-analysis of 12 association studies involving 2836 IS cases and 3354 control subjects, we used a more stringent inclusion method and summarized data on the association of eNOS T-786C polymorphism and IS susceptibility. Results: We found a significantly lowered IS risk under the CC vs. TT genetic model (odds ratio, OR = 0.53, 95% confidence interval, CI = 0.29–0.98, p = 0.160, I2 = 45.5%) by random effects model in Caucasians and under the allele model C vs. T (OR = 0.42, 95% CI = 0.21–0.87) by fixed effects model in African-Americans. In addition, a significant increased risk of IS was observed in Asians (C vs. T: OR = 1.14, 95% CI = 1.02–1.28, p = 0.990, I2 = 0.0%) by fixed effects model. Stratified analysis by mean age also showed that the allele C carriers, compared with the allele T allele carriers, had higher risk of suffering IS (OR = 1.16, 95% CI = 1.03–1.31) in the population of 60–65 years without heterogeneity. Conclusions: The combined results suggest that eNOS T-786C polymorphism may be associated with IS susceptibility among the population between 60 and 65 years in particular.